Estudio geológico- geotécnico del tramo de Vía Nueva Fátima- Numbiaranga- Portachuelo de los cantones Sozoranga y Macará, provincia de Loja. - Ochoa Tapia, Maritza Ximena (2013)
This research work is executed him in the cantons Sozoranga and Macará of the Province of Loja, which hosted a Geological Survey - New road Geotechnical Fatima - Numbiaranga - Portachuelo with the view of determining whether the section of track above named, provided geological features - geotechnical suitable for future improvement and expansion in productive development provisions, livestock and tourism sector, since this is a third order road axis. The methodology for the implementation of research work is based on three levels: the first level consisted of collecting bibliography information for the study area and bibliographic support regarding theoretical concepts. The second level consisted of field work and data collection site where conducted topographic surveys, geological and structural geological measures and collecting soil and rock samples. The third level was based purely on the interpretation of any information obtained as bibliographic information, topographic, geological and structural interpretation of field and laboratory results on samples of rocks and soils. As a result of this study it was found that the way New Fatima - Numbiaranga - Portachuelo if given geological conditions - geotechnical suitable for improvement, considering that for the design of asphalt address all of the parameters calculated in the present investigation.